PENGARUH JUMLAH JET HOLE DAN DIAMETER INNER PIPE TERHADAP UNJUK KERJA KOMPOR ALKOHOL - Irwan Humaidi; Ida Bagus Alit; I Made Nuarsa (Universitas Mataram, 2013)
Alcohol is an renewable alternative fuel produced from plants material. Plants usually contains essence such as : cassava, yam, corn, and sago palm essence. Processing for producing alcohol begin from hydrolysis process, that is essence converts to glucose then fermentation process to converting glucose to ethanol and CO2. After fermentation process ends, we continue to destilation process to decomposing alcohol based on its boiling point.This research aims to know design of alcohol stove design by variating its jet hole quantity and inner pipe diameters. Duration of heating, heat dropped, fuel consumption, and alcohol-stove efficiency are attentioned variables in this research. Combustion process of alcohol-stove begin with entering fuel to fuel tube then firing up the stove by striking fire on weep hole in inner pipe, combustion will increasing stove temperature and steam the alcohol. The steam will turn out through the jet hole so the stove flame is stable.This research result shows have been showing the stove most optimum showed by alcohol stove with 1 ½ inch inner pipe diameter variation with most jet hole is 8 holes, because the efficience at variation of this stove is high and the burning time it quick also. The greatest quantity of fuel consumption with variety of jet hole 16 amount with 1 ½ inch diameter that is 0.1061 ml/second. Whereas the bigest stove efficiency contained in stove with inner pipe diameter variety 1 ¼ inch with amount of jet hole 8 that is 48,33%.